1984
DOI: 10.1093/jnci/72.1.161
|View full text |Cite
|
Sign up to set email alerts
|

B16 Murine Melanoma and Aging: Slower Growth and Longer Survival in Old Mice23

Abstract: The growth characteristics and colonization potential of a transplantable melanoma administered to young (3 mo) and old (24 mo) C57BL/6 mice were investigated. After sc injection of B16-F10 melanoma cells, tumor growth was slower, and final tumor volume was less in the older mice. Furthermore, after iv injection of B16-F1 melanoma cells, the number of pulmonary colonies was also less, and the survival was greater in the older mice. These findings indicate an age advantage in this experimental tumor model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 0 publications
1
43
2
Order By: Relevance
“…Immunosenescence is believed to be one possible reason for increased incidence of most types of cancer in aging humans and animals (Anisinov, 1987). There is now good clinical and experimental evidence indicating a difference in the growth rate of primary tumors and in the incidence of metastases with age (Ershler et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Immunosenescence is believed to be one possible reason for increased incidence of most types of cancer in aging humans and animals (Anisinov, 1987). There is now good clinical and experimental evidence indicating a difference in the growth rate of primary tumors and in the incidence of metastases with age (Ershler et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs commonly in normal animal tissue (embryonic growth, wound healing, local inflammatory reactions) [1,9] as well as in abnormal tissue such as seen in the growth of neoplastic tissue [10]. We have recently observed that certain weakly antigenic murine tumors (B16 melanoma and Lewis Lung carcinoma) grow more slowly in old animals when compared to young [4][5][6]. When examined histologically, one characteristic of these tumors in old animals is their relatively low number of blood vessels [16].…”
Section: Introductionmentioning
confidence: 99%
“…But at this time, evidence from prospective randomized trials that geriatric assessment improves the care for elderly patients with cancer is still missing. [2].…”
Section: Oncology: Characteristics Of Elderly Patientsmentioning
confidence: 99%